Particularity Analysis Of Sediment Deposits And Sediment Rates In The Wiso River In Jepara Regency): Analisa Partikularitas Endapan Sungai Wiso Kabupaten Jepara - Triyano, Al; Rochmanto, Decky; Adi Saputro, Yayan (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2021)
The sedimentation process that occurs continuously will cause silting due to sedimentation which affects the decrease in capacity flow of river particles. Sedimentary particles carried by the river flow heading to the sea will cause deposition in the estuary area so that it will blocking the flow of rivers to the sea. Based on the data from the sediment sample test results, gradation of sediment particles in the Wiso river consists of fine sand (Fine Sand) to very fine silt (Very Fine Silt) the average soil type is silt and the value of The density of the sediment has an average of 2,613. As well as for the benefits of this type of Sedimentation can be used as a water-resistant material for reservoirs and construction dam building.